THE POTENCY OF ANGLE MEASUREMENT AND COMPARISON OF VEIN LENGTHS IN DISTINGUISHING BACTROCERA SPECIES COMPLEXES - Pratyadhiraksana, Gesang; Murniningtyas Puji Lestari, Tri; Hari Murti, Rudi; ., Suputa (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
The potency of angle measurement and comparison of vein lengths in distinguishing Bactrocera species complexes. One of the most conspicuous features of Bactrocera fruit flies is their wing, which can be elaborated for identification. The distinctive wing patterns are used to separate species and classify species complexes. The wing shape can be used as a potential discriminator between closely related taxa. To develop wing applications in taxonomy, in this study, the degree measure of angles and the comparisons of vein lengths were investigated quantitatively to distinguish among important pest quarantine species of the Bactrocera dorsalis complex: B. dorsalis and B. carambolae; the B. frauenfeldi complex: B. frauenfeldi and B. albistrigata; and a species belonging to subgenus Zeugodacus, B. cucurbitae. The result showed that species complexes were clustered into significantly different groups based on the degree measure of cell br and the comparison between r-m and dm-cu cross-vein length. This conclusive evidence was supported by phylogenetic analysis using COI gene. This present result indicated that the cell br angle measure and the comparison between r-m and dm-cu vein length could be applied to distinguish species complexes in genus Bactrocera.